Foliar nutrient evolution in three mango cultivars in Nayarit, Mexico - Castro-López, Mariela Guadalupe; Salazar-García, Samuel; González-Durán, Isidro José Luis; Medina-Torres, Raúl; González-Valdivia, José (Revista Mexicana de Ciencias Agrícolas, 2018)
In order to develop site-specific fertilization programs for t mango production, it ́s necessary to have proper information for each producing-region. The aim of this study was to determine the evolution of macro and micronutrients through the life of the leaves of the cultivars ́ vegetative flushes Ataulfo, Kent and Tommy Atkins. The orchards were located in four municipalities in the State of Nayarit with sub-humid warm climate, at elevations of 11 to 601 m and average annual temperature of 21.7 to 22.7 °C. In each orchard, 20 trees were randomly selected and, in each of them 20 newly emerged shoots were marked from each vegetative flush. Leaf samples were taken monthly from emergence to leaf abscission and, the concentrations of N, P, K, Ca, Mg, S, Fe, Cu, Mn, Zn and B were determined on the dry matter. In order to describe the evolution of each nutrient, the concentration for each day of the leaf was predicted using mathematical functions. Two vegetative growth flushes were recorded for both, ‘Ataulfo’ and ‘Kent’ (spring and summer) and ‘Tommy Atkins’ (spring and fall). The evolution of macro and micronutrients varied between cultivars and was inf luenced by the vegetative f lush and phenological phase. In the three cultivars studied, the nutrient evolution of spring flush was more affected by the later stages of f lower development (from the caulif lower stage to anthesis). In the case of the second vegetative flush (summer or fall) the nutrient evolution was more affected by fruit ́s growth.
Keywords: Mangifera indica; Ataulfo; vegetative f lushes; Tommy Atkins; Kent